Sectoral Allocation by Gender of Latin American Workers over the Liberalization Period of the 1990s - Cunningham, Wendy V. (World Bank, Washington, DC, 2014)
The recent restructuring of Latin American economies has renewed interest in the effects of trade liberalization, on labor markets, and on the gender division of labor. The author does not attempt to establish casuality between economic reforms, and the types of jobs that men and women hold. Instead, she provides a detailed description of the trends in male, and female formal, and informal sector participation during the economic reform period in Argentina, Brazil, and Costa Rica. The author first compares the gender composition of the formal, informal wage, and self-employment sectors in a year before reforms (1988 for Argentina, 1989 for Brazil, and Costa Rica), and a year after reforms implementation (1997 for Argentina, 1995 for Brazil and Costa Rica). Although women continued to be more likely than men to work in the informal wage sector, there is no trend of "masculinization" or "feminization" of the informal sector, or any other. Instead, in Argentina men have overtaken women as the most prevalent workers in the informal wage sector, while in Brazil, the opposite has occurred (as men move into self-employment). In Costa Rica there have been no statistical, observable changes. The author then considers the distribution across sectors within each gender group, to identify whether men, and women are more likely to select different sectors in the post-reform period relative to the pre-reform period. Among both men, and women in all three countries (except Brazilian men), workers have become more likely to hold informal wage jobs, and less likely to hold formal sector jobs. Trends in human capital accumulation explain these changes for both men, and women, while changes in gender roles, primarily in homecare and marriage, do not seem to have an effect.